Improved Crop Yield Forecasting using Wavelet-Based Denoising and Artificial Neural Networks Framework - Md Yeasin; Ranjit Kumar Paul; Pushkar Bora; Himadri Shekhar Roy; Prakash Kumar; A.K. Paul (Journal of the Indian Society of Agricultural Statistics, 2026)
Agricultural crop yields are often non-stationary, noisy and influenced by multiple environmental factors, which limits the effectiveness of traditional statistical models. Advanced hybrid approaches that can capture both linear and non-linear patterns, along with multi-scale characteristics, are required for reliable forecasting. This study aimed to develop and evaluate a hybrid wavelet-based forecasting framework by integrating the Maximal Overlap Discrete Wavelet Transform (MODWT) with Artificial Neural Network (ANN) and Autoregressive Integrated Moving Average (ARIMA) models for predicting crop yield series of Total Pulses, Gram, and Tur in India. Annual yield data from 1950 to 2023 were analysed using a hybrid modelling framework. The MODWT was applied to decompose the original time series into multi-resolution components, followed by denoising through thresholding techniques. The decomposed components were then modelled using ANN and ARIMA. Optimal wavelet filters and decomposition levels were obtained based on predictive performance. The results showed that hybrid wavelet-based models significantly outperformed standalone ARIMA and ANN models. This study contributes to the literature by systematically optimizing wavelet filters and decomposition levels within a hybrid modelling framework and demonstrates the effectiveness of combining wavelet-based denoising with machine learning and statistical models for non-stationary agricultural time series data.